Minimal whey protein with carbohydrate stimulates muscle protein synthesis following resistance exercise in trained young men - Tang, J. E.; Manolakos, J. J.; Kujbida, G. W.; Lysecki, P. J.; Moore, D. R.; Phillips, S. M. (Applied Physiology, Nutrition, and Metabolism, 2007)
Whey protein is a supplemental protein source often used by athletes, particularly those aiming to gain muscle mass; however, direct evidence for its efficacy in stimulating muscle protein synthesis (MPS) is lacking. We aimed to determine the impact of consuming whey protein on skeletal muscle protein turnover in the post-exercise period. Eight healthy resistance-trained young men (age = 21 ± 1 .0 years; BMI = 26.8 ± 0.9 kg/m2 (means ± SE)) participated in a double-blind randomized crossover trial in which they performed a unilateral leg resistance exercise workout (EX: 4 sets of knee extensions and 4 sets of leg press; 8-10 repetitions/set; 80% of maximal), such that one leg was not exercised and acted as a rested (RE) comparator. After exercise, subjects consumed either an isoenergetic whey protein plus carbohydrate beverage (WHEY: 10 g protein and 21 g fructose) or a carbohydrate-only beverage (CHO: 21 g fructose and 10 g maltodextran). Subjects received pulse-tracer injections of l-[ring-2H5]phenylalanine and l-[15N]phenylalanine to measure MPS. Exercise stimulated a rise in MPS in the WHEY-EX and CHO-EX legs, which were greater than MPS in the WHEY-RE leg and the CHO-RE leg (all p < 0.05), respectively. The rate of MPS in the WHEY-EX leg was greater than in the CHO-EX leg (p < 0.001). We conclude that a small dose (10 g) of whey protein with carbohydrate (21 g) can stimulate a rise in MPS after resistance exercise in trained young men that would be supportive of a positive net protein balance, which, over time, would lead to hypertrophy.